2013
DOI: 10.1002/ijc.28049
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's lymphoma mortality in the Americas, 1997–2008: Achievements and persistent inadequacies

Abstract: Although therapeutic advancements have made Hodgkin's lymphoma (HL) a largely curable disease, trends in HL mortality have been variable across countries. To provide updated information on HL mortality in the Americas, overall and 20–44 years age‐standardized (world population) mortality rates from HL were derived for the 12 Latin American countries providing valid data to the World Health Organization database and with more than two million of inhabitants. For comparative purpose, data for the United States a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Randomized clinical trials conducted by cooperative groups in North America and Europe have identified treatment schedules that provide higher efficacy and lower toxicity. However, data about HL in developing countries are scarce and come mostly from retrospective series . These data suggest that there are substantial disparities in healthcare and treatment outcomes for HL patients in large areas of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized clinical trials conducted by cooperative groups in North America and Europe have identified treatment schedules that provide higher efficacy and lower toxicity. However, data about HL in developing countries are scarce and come mostly from retrospective series . These data suggest that there are substantial disparities in healthcare and treatment outcomes for HL patients in large areas of the world.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of Hodgkin's lymphoma (HL) has markedly improved over the past few decades, making HL one of the cancers with the greatest chances of cure . However, data about HL in developing countries are limited and come mostly from retrospective series . These data suggest the existence of substantial disparities in health care and treatment outcomes for HL patients in large areas of the world.…”
mentioning
confidence: 99%
“…1 However, data about HL in developing countries are limited and come mostly from retrospective series. [2][3][4][5][6] These data suggest the existence of substantial disparities in health care and treatment outcomes for HL patients in large areas of the world.…”
mentioning
confidence: 99%
“…Furthermore, mortality from several cancers highly curable with medical therapies including testicular cancer [7, 13], Hodgkin’s lymphomas [6, 7] and leukemias [10, 14] remains higher in Central and Eastern Europe compared with Western Europe [7], but also compared with North America and selected major countries of South America, including Brazil and Argentina [15]. Likewise, although some decline in breast cancer mortality—another neoplasm largely amendable to cure—has been observed in recent years in Central and Eastern Europe [16], this decline has been smaller than that in Western Europe.…”
mentioning
confidence: 99%
“…An increase in cancer control expenditure would most likely have a favorable effect on cancer mortality in Central and Eastern Europe. However, it is now clear that countries such as Brazil and Argentina, with gross national per capita products comparable to or, in some instances, lower than those in several Central and Eastern European countries, have achieved a better management in highly treatable cancers, such as Hodgkin’s lymphoma [15] than that achieved by several countries in Central and Eastern Europe. Besides expenditure, therefore, several measures aimed at improving clinical management (addressing gaps in specialty training and facilities from pathological diagnosis to multidisciplinary treatments), and optimizing cancer control (such as antismoking measures), as outlined by Vrdoljak et al [2], are required to reduce cancer rates in Central and Eastern Europe to levels comparable with those in other high-income countries.…”
mentioning
confidence: 99%